2017
DOI: 10.1021/acs.orglett.7b03256
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Synthesis of γ-Lactones from Alkenes: High-Resolution Mass Spectrometry as a Tool To Study Photoredox Reactions

Abstract: A mild photocatalytic manifold for the synthesis of γ-lactones has been developed. Utilizing Ru(bpy)Cl as the photocatalyst, a cheap and reproducible synthetic protocol for γ-lactones has been introduced. Mechanistic studies revealed the successful monitoring of photocatalytic reactions and radical intermediates via high-resolution mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 68 publications
7
42
0
1
Order By: Relevance
“…By using eosin B as photocatalyst, bases, including NaHCO 3 , K 2 CO 3 , Cs 2 CO 3 , K 3 PO 4 , 2,6-lutidine, TBD DBU, TMG, and Et 3 N were screened, respectively (entries [8][9][10][11][12][13][14][15][16]. The results indicated that DABCO was superior to the others (entry 6 vs entries [8][9][10][11][12][13][14][15][16]. Surprisingly, the yield of 3 a was significantly improved to 70% when the reaction was conducted in open air by using eosin B (5 mol%) and sub-stoichiometric amounts of DABCO (50 mol%) (entry 17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using eosin B as photocatalyst, bases, including NaHCO 3 , K 2 CO 3 , Cs 2 CO 3 , K 3 PO 4 , 2,6-lutidine, TBD DBU, TMG, and Et 3 N were screened, respectively (entries [8][9][10][11][12][13][14][15][16]. The results indicated that DABCO was superior to the others (entry 6 vs entries [8][9][10][11][12][13][14][15][16]. Surprisingly, the yield of 3 a was significantly improved to 70% when the reaction was conducted in open air by using eosin B (5 mol%) and sub-stoichiometric amounts of DABCO (50 mol%) (entry 17).…”
Section: Resultsmentioning
confidence: 99%
“…[14] The recently developed visible-light photoredox catalysts include ruthenium and iridium polypyridyl complexes and organic dyes, which efficiently facilitated the conversion of visible-light into chemical energy under extremely mild conditions. [15] In spite of the excellent photocatalytic properties of ruthenium and iridium polypyridyl complexes in organic synthesis, the metal complexes are usually expensive and potentially toxic. In contrast, organic dyes are an attractive alternative to the transition metal complexes as photoredox catalysis in that they are usually less expensive, less toxic, and easier to handle.…”
Section: Introductionmentioning
confidence: 99%
“…If we attempted to employ styrene as the olefin partner, in the exact same conditions, we could only observe polymerization events to occur (Scheme A). This is in accordance with our previous postulation and findings that a different mechanism is in place if an aryl versus an alkyl substituent on the olefin is employed and whether sodium ascorbate is added or not . To verify this, we performed the reaction as described in literature, and indeed, the product bearing the ether was obtained in 78 % yield (Scheme B).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kokotos and co-workers published a visible light photoredox catalyzed lactone formation from iodoacetic acid and alkenes [29] (Scheme 1). In addition, it has been shown that monochloroacetic acid can be reduced by hydrated electrons [30,31].…”
Section: Introductionmentioning
confidence: 99%